Real‐world experience with limited screening for occult malignancy in patients presenting with spontaneous venous thromboembolism: a single‐centre, retrospective cohort study. Issue 3 (20th March 2022) - Grainger, Brian T.; McCrea, Te Apatuoterangi; Eaddy, Nicola; Ockelford, Paul; Young, Laura
Abstract: Spontaneous venous thromboembolism (VTE) may represent the first manifestation of previously undiagnosed malignancy; however, contemporary international guidelines call for a limited approach to screening for malignancy in such patients. This retrospective cohort study of 328 patients presenting to the Auckland City Hospital Thrombosis Unit identified 17 patients who were subsequently diagnosed with some form of malignancy within 12 months of their presentation. Review of their history, physical examination and limited age and gender‐appropriate cancer screening investigations as described by the National Institute for Clinical Excellence and International Society of Thrombosis and Haemostasis guidelines revealed that all 17 would have been safely diagnosed by the 'limited' screening approach endorsed by these guidelines, thus presenting a 'real‐world' basis for clinicians to pursue 'limited' screening for malignancy in their everyday practice in patients with spontaneous VTE.